A systematic review of gender in participatory and social learning research in agriculture and land management in Africa - Peter Asare-Nuamah; Peter Asare-Nuamah; Peter Asare-Nuamah; David Anaafo; Tina Beuchelt; Constance A. Akurugu (Frontiers in Sustainable Food Systems)
We conduct a systematic review to explore the state of knowledge on participatory and social learning research in agriculture and land management in Africa, the extent to which women and other marginalized groups are engaged in the collective development processes, and how gender issues are addressed. Grounded in gender and social inclusion concepts, guided by Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA), and using Scopus and Web of Science databases, we discover a modest and fluctuating growth in participatory and social learning research since 2005. However, many participatory studies, do not address specifically collective learning and reflection nor integrate gender. For those with in-depth gender focus, multiple approaches are adopted for stakeholder selection and engagement, enabling a detailed reflection and integration of gender dimensions in co-developing solutions. It is crucial for participatory studies to be socially inclusive and gender sensitive, and address power dynamics, which are necessary to alter gender relations and norms, tackle inequality, and enhance agency at the household and community levels.